2013
DOI: 10.1166/jnn.2013.5998
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Power of a Single-Walled Carbon Nanotubes Rope

Abstract: In this work, a rope of single-walled carbon nanotubes is prepared by using a diamond wire drawing die. At atmospheric condition, the electrical conductance and the thermoelectric voltage of single-walled carbon nanotubes rope have been investigated with the hot-side temperature ranging from 292 to 380 K, and cold-side temperature at 292 K. For different temperatures in the range of 292 to 380 K at hot-side, the current-voltage curves are almost parallel to each other, indicating that the electrical conductanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…To avoid damage to the samples, the laser power was set to be less than 1 mW. An ∼1 μm laser spot can be obtained with the application of a 100× objective lens with a numerical aperture of 0.90 . From the intensity ratio of G and 2D modes of the as-grown GF, it can be concluded that the walls of the GF are composed of monolayer to few-layer graphene sheets (Supporting Information, Figure S2).…”
Section: Experiments Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid damage to the samples, the laser power was set to be less than 1 mW. An ∼1 μm laser spot can be obtained with the application of a 100× objective lens with a numerical aperture of 0.90 . From the intensity ratio of G and 2D modes of the as-grown GF, it can be concluded that the walls of the GF are composed of monolayer to few-layer graphene sheets (Supporting Information, Figure S2).…”
Section: Experiments Sectionmentioning
confidence: 99%
“…Harvesting energy from the ambient environment directly is one of the most promising and effective approaches for powering nano/micro electromechanical systems (N/MEMS), including ultrasensitive chemical sensors, implantable biosensors, portable/wearable personal electronics, and even remote and mobile environmental sensors. , Carbon nanomaterials, which are responsible for the conversion of some ambient energy into electrical energy directly, have attracted much attention recently. It has been demonstrated that the flow of polar liquids over carbon nanotubes (CNTs) can generate a net potential difference and associated electric current in the nanotubes along the flow direction. The induced voltage increases with flow velocity to a saturated value that depends on the ionic conductivity and the polar nature of liquids.…”
Section: Introductionmentioning
confidence: 99%
“…However, such high filler loadings may result also in a significant increase of thermal conductivity [15,26,27]. In addition, studies on carbon nanotubes (CNTs) only films (as bucky papers) have shown promising thermoelectric behavior which has been found to be related to the level of doping [28,29], as well as the dopant nature [30][31][32][33][34]. Doping of the SWCNTs by using e.g.…”
Section: Introductionmentioning
confidence: 99%
“…65 However, due to the metallic nature of the SWNTs with the expected inherently high thermal conductivity and low Seebeck coefficient, the composite made solely by CNTs does not provide a respectable thermoelectric efficiency. [66][67][68] Consequently, extensive effort in this field Thermoelectric properties at room temperature and compositions of the hetero--structures and the control samples in refs. 62 and 63.…”
Section: Other Hybrid Hetero--structures 41 Carbon Nanotube (Cnt)--bmentioning
confidence: 99%